Sexual and reproductive health among forcibly displaced persons in urban environments in low and middle-income countries: scoping review findings - Logie, Carmen H.; MacKenzie, Frannie; Malama, Kalonde; Lorimer, Nicole; Lad, Anoushka; Zhao, Michelle; Narasimhan, Manjulaa; Fahme, Sasha; Turan, Bülent; Kagunda, Julia; Konda, Kelika; Hasham, Aryssa; et al. (Reproductive health, 2024)
Background Most forcibly displaced persons are hosted in low- and middle-income countries (LMIC). There is a growing urbanization of forcibly displaced persons, whereby most refugees and nearly half of internally displaced persons live in urban areas. This scoping review assesses the sexual and reproductive health (SRH) needs, outcomes, and priorities among forcibly displaced persons living in urban LMIC. Methods Following The Joanna Briggs Institute scoping review methodology we searched eight databases for literature published between 1998 and 2023 on SRH needs among urban refugees in LMIC. SHR was operationalized as any dimension of sexual health (comprehensive sexuality education [CSE]; sexual and gender based violence [GBV]; HIV and STI prevention and control; sexual function and psychosexual counseling) and/or reproductive health (antental, intrapartum, and postnatal care; contraception; fertility care; safe abortion care). Searches included peer-reviewed and grey literature studies across quantitative, qualitative, or mixed-methods designs. Findings The review included 92 studies spanning 100 countries: 55 peer-reviewed publications and 37 grey literature reports. Most peer-reviewed articles ( n = 38) discussed sexual health domains including: GBV ( n = 23); HIV/STI ( n = 19); and CSE ( n = 12). Over one-third ( n = 20) discussed reproductive health, including: antenatal, intrapartum and postnatal care ( n = 13); contraception ( n = 13); fertility ( n = 1); and safe abortion ( n = 1). Eight included both reproductive and sexual health. Most grey literature ( n = 29) examined GBV vulnerabilities. Themes across studies revealed social-ecological barriers to realizing optimal SRH and accessing SRH services, including factors spanning structural (e.g., livelihood loss), health institution (e.g., lack of health insurance), community (e.g., reduced social support), interpersonal (e.g., gender inequitable relationships), and intrapersonal (e.g., low literacy) levels. Conclusions This review identified displacement processes, resource insecurities, and multiple forms of stigma as factors contributing to poor SRH outcomes, as well as producing SRH access barriers for forcibly displaced individuals in urban LMIC. Findings have implications for mobilizing innovative approaches such as self-care strategies for SRH (e.g., HIV self-testing) to address these gaps. Regions such as Africa, Latin America, and the Caribbean are underrepresented in research in this review. Our findings can guide SRH providers, policymakers, and researchers to develop programming to address the diverse SRH needs of urban forcibly displaced persons in LMIC. Plain English summary Most forcibly displaced individuals live in low- and middle-income countries (LMICs), with a significant number residing in urban areas. This scoping review examines the sexual and reproductive health (SRH) outcomes of forcibly displaced individuals in urban LMICs. We searched eight databases for relevant literature published between 1998 and 2023. Inclusion criteria encompassed peer-reviewed articles and grey literature. SRH was defined to include various dimensions of sexual health (comprehensive sexuality education; sexual and gender-based violence; HIV/ STI prevention; sexual function, and psychosexual counseling) and reproductive health (antenatal, intrapartum, and postnatal care; contraception; fertility care; and safe abortion care). We included 90 documents (53 peer-reviewed articles, 37 grey literature reports) spanning 100 countries. Most peer-reviewed articles addressed sexual health and approximately one-third centered reproductive health. The grey literature primarily explored sexual and gender-based violence vulnerabilities. Identified SRH barriers encompassed challenges across structural (livelihood loss), health institution (lack of insurance), community (reduced social support), interpersonal (gender inequities), and individual (low literacy) levels. Findings underscore gaps in addressing SRH needs among urban refugees in LMICs specifically regarding sexual function, fertility care, and safe abortion, as well as regional knowledge gaps regarding urban refugees in Africa, Latin America, and the Caribbean. Self-care strategies for SRH (e.g., HIV self-testing, long-acting self-injectable contraception, abortion self-management) hold significant promise to address SRH barriers experienced by urban refugees and warrant further exploration with this population. Urgent research efforts are necessary to bridge these knowledge gaps and develop tailored interventions aimed at supporting urban refugees in LMICs.